Assessment of the efficacy of a novel tailored vitamin K dosing regimen in lowering the International Normalised Ratio in over‐anticoagulated patients: a randomised clinical trial. (2nd August 2017) - Kampouraki, Emmanouela; Avery, Peter J.; Wynne, Hilary; Biss, Tina; Hanley, John; Talks, Kate; Kamali, Farhad
Summary: Current guidelines advocate using fixed‐doses of oral vitamin K to reverse excessive anticoagulation in warfarinised patients who are either asymptomatic or have minor bleeds. Over‐anticoagulated patients present with a wide range of International Normalised Ratio (INR) values and response to fixed doses of vitamin K varies. Consequently a significant proportion of patients remain outside their target INR after vitamin K administration, making them prone to either haemorrhage or thromboembolism. We compared the performance of a novel tailored vitamin K dosing regimen to that of a fixed‐dose regimen with the primary measure being the proportion of over‐anticoagulated patients returning to their target INR within 24 h. One hundred and eighty‐one patients with an index INR > 6·0 (asymptomatic or with minor bleeding) were randomly allocated to receive oral administration of either a tailored dose (based upon index INR and body surface area) or a fixed‐dose (1 or 2 mg) of vitamin K. A greater proportion of patients treated with the tailored dose returned to within target INR range compared to the fixed‐dose regimen (68·9% vs. 52·8%; P = 0·026), whilst a smaller proportion of patients remained above target INR range (12·2% vs. 34·0%; P < 0·001). Individualised vitamin K dosing is more accurate than fixed‐dose regimen in lowering INR to within target range in excessively anticoagulated patients.